Números y secuencias aleatorias: aplicaciones - VARIA, Stella; CONTINI, Liliana; CARRERA, Elena; TABORDA, Lilian (UNION MATEMATICA ARGENTINA, 2003)
Docentes de la Fac.Bioquímica y Cs.Biológicas de la U.N.L. y U.T.N., de Paraná